Anti-AGEing defences against Alzheimer's disease. (1st December 2003) - Münch, G.; Kuhla, B.; Lüth, H.-J.; Arendt, T.; Robinson, S.R.
Abstract : Accumulation of insoluble protein deposits and their cross-linking by AGEs (advanced glycation end products) in the brain is a feature of aging and neurodegeneration, especially in AD (Alzheimer's disease). In AD, two types of fibrillar protein aggregates are present: extracellular deposits (plaques) consisting mainly of Aβ (β-amyloid peptide), and intracellular deposits (tangles) composed predominantly of microtubule-associated protein tau. Both plaques and tangles are modified by AGEs, which occurs particularly at lysine and arginine residues. Interaction of a synthetic amyloid plaque (fibrillar Aβ) with microglia leads to a strong pro-inflammatory response, indicating that priming of immune cells with β-amyloid potentiates their response to secondary stimuli such as AGE and cytokines such as interferon-γ. Formation of hyperphosphorylated and cross-linked microtubule-associated protein tau aggregates, especially tau dimers as the first step in tangle formation, can be induced in vitro by the combination of okadaic acid, a PP2A phosphatase inhibitor, and methylglyoxal. These results suggest that excess production of reactive carbonyl compound ('carbonyl stress') and subsequent AGE formation can contribute to cross-linking of protein fibrils and to pathological pro-inflammatory signalling, which all contribute to pathological changes and dementia progression in AD. However, the human brain has developed the glyoxalase system, a most effective defence system to scavenge small dicarbonyl compounds such as glyoxal and methylglyoxal. Very importantly, this system needs GSH as a rate-limiting cofactor. Since GSH is limited under conditions of oxidative stress and inflammation, supplementation with antioxidants such as lipoic acid, vitamin E or flavonoids could indirectly strengthen the anti-glycation defence system in AD. In addition, synthetic carbonyl scavengers and anti-inflammatory drugs could also be valuable drugs for the 'anti-glycation' treatment of AD.